Evaluation of sprint biomechanics by means of an instrumented training sledge in soccer - Petrone, N.; Marcolin, G.; Tolin, A. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The aim of the study was the functional evaluation of sprint biomechanics by means of an instrumented training sledge in a soccer field. In particular, peak values of the horizontal ground reaction force generated in the first 6 thrusts were estimated after measuring the instantaneous cable tension and the sledge acceleration with a data acquisition system installed on the sledge. Three soccer players were asked to perform 3 couples of 30m sprints (starting once with the left and once with the right leg) while pulling the training sledge: the sledge mass increased in three levels (11.5kg, 16.5kg, 21.5kg). The athletes performed also Bosco tests in monolateral CMJ. Differences in force values between the two legs were more evident after the sledge functional testing in the field than after Bosco monolateral CMJ: the method can suggest functional training procedures to improve the strength of the weak leg and running coordination.